Leadership Styles And Team Cohesiveness: A Study Based On Non Managerial Level Employees In Public Sector Organizations In Sri Lanka - Hemakumara, M.G.G. (My University, 2011)
This study aims to identify the relationship between the directive and supportive leadership styles and the team cohesiveness if any. The identified research problem is whether there is any relationship between leadership styles and team cohesiveness exists in the public sector organizations in Sri Lanka? Accordingly three objectives of the study are; to identify the relationship between directive leadership style and team cohesiveness, to identify the relationship between supportive leadership style and team cohesiveness and to identify which leadership is highly impact to develop team cohesiveness. The selected sample consists of 73 non managerial employees of public sector, those who employed in various public sector institutions in the Colombo district in Sri Lanka. A questionnaire was used to collect primary data, from the sample. The Person correlation analysis was used to data analysis and hypothesis testing. According to the correlation results, both directive and supportive leadership styles have indicated positive relationship with team cohesiveness, but supportive leadership has a strong relationship with the team cohesiveness.